Experience with the use of gelatin tannate in complex therapy in patients with a new coronavirus infection COVID-19 - Y. N. Moskaleva; Y. B. Khamanova; A. V. Chashchina; L. A. Shmalts; A. I. Perin (Лечащий Врач)
The new coronavirus infection COVID-19 is a systemic disease associated with the involvement in the pathological process not only of the lungs with the development of respiratory failure, but also of cells of the gastrointestinal tract, which causes dysbiosis of the intestinal microbiota, thereby contributing to the development of interstitial inflammation in the intestinal wall. The purpose of our research was to evaluate the effectiveness of the use of the gelatin tannate in intestinal lesions in patients with a new coronavirus infection COVID-19. The study included 58 patients diagnosed with a new coronavirus infection COVID-19 aged 35 to 70 years, hospitalized in the infectious hospital of the State Autonomous Healthcare Institution of the Sverdlovsk region "City Clinical Hospital No. 40" of Yekaterinburg. The patients were divided into 2 groups: the main group (n = 26) of people who received gelatin tannate in the complex therapy, the second group (control, n = 32) who did not receive the cytomucoprotector Adiarin in the complex therapy. The study included the patients with COVID-19 infection with gastrointestinal manifestations confirmed by the results of the analysis of a smear from the nasopharynx and oropharynx for SARS-CoV-2 coronavirus by polymerase chain reaction. The exclusion criteria from the study were age over 70 years, concomitant pathology: diseases of the musculoskeletal system, chronic kidney disease, pregnancy, infection caused by the human immunodeficiency virus, oncohematological and lymphoproliferative diseases. Against the background of taking of gelatin tannate, the following phenomena were observed in the main group in comparison with the control group: a decrease in the duration of febrile syndrome by 1.2 times, diarrheal syndrome by 2.5 times, dyspeptic syndrome by 1.8 times; correlation between the frequency and duration of diarrheal syndrome and the severity of interstitial inflammation in the intestinal wall (r = 0.7, p < 0.01); immunomodulatory effect on the T-cell link of immunity. No side effects were observed.